Disrupting Social Exclusion in the Museum Through the Use of Rock as a Place of Memory - Flores Varela, María Isabel (Eikón / Imago, 2019)
The majority of people prefer to go to the movies rather than to a museum. This is not surprising given the image of a high-cultured, history-based, representation-controlled museum-cemetery that pervades in the collective imaginarium. We can admit that the museum as a whole, is affected by a set of wicked problems, and one resonates pretty loud: the social exclusion. There are many forces that have facilitated the social exclusion in the museum. In this article, I would like to share the results of my research, “Rock as a place of memory,” in which I analyze how history has superseded memory through the museum ́s genealogy and propose the transformation of rock music into a place of memory as a tool to disrupt social exclusion of the museum.